EVALUASI PROGRAM DALAM MENGATASI PENGANGGURAN OLEH DINAS TENAGA KERJA KOTA PEKANBARU TAHUN 2023 - Syahbana, Afif Sahru Ali; Harirah, Zulfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to evaluate unemployment alleviation programs by the Pekanbaru City Manpower Office in 2023 in order to overcome the problem of high and low unemployment rates and decreasing labor absorption rates in Pekanbaru City in 2023. This research was conducted using qualitative descriptive methods and techniques. Data collection carried out in research is interviews, documentation, note-taking and recording. The theory used is the CIPP Model Program Evaluation by Stufflebeam. The results of this research indicate that unemployment alleviation programs by the Manpower Department are not implemented optimally due to ineffective and efficient budget allocations, lack of sufficient Human Resources (HR) and experts in implementing programs, inadequate facilities and infrastructure. , lack of information about the program to job seekers, and minimal company participation in the program. So, the conclusion is that there needs to be sufficient budget allocation for the implementation of all programs, the government needs to continue to make progressive and innovative efforts so that existing obstacles can be minimized so that the program can still be implemented, a firm and pro-active attitude in establishing good relations with companies, and active participation and supervision from the community regarding program implementation so that in the future all programs can be fully implemented and have a more significant impact in overcoming unemployment in Pekanbaru City. Keywords: Program Evaluation, Unemployment, Manpower Department, Pekanbaru City